Deep winds beneath Saturn’s upper clouds from a seasonal long-lived planetary-scale storm - Sánchez-Lavega, A.; Río-Gaztelurrutia, T. del; Hueso, R.; Gómez-Forrellad, J. M.; Sanz-Requena, J. F.; Legarreta, J.; García-Melendo, E.; Colas, F.; Lecacheux, J.; Fletcher, L. N.; Barrado-Navascués, D.; Parker, D. (Nature (London), 2011)
Storm brewing on Saturn's sixth giant storm Six Great White Spot (GWS) events have been observed in the atmosphere of Saturn since 1876. These giant convective storms occur roughly once every Saturnian year (equal to 29.5 Earth years). The sixth GWS erupted in December 2010 and has been the subject of intense observation. Two papers in this issue present the details of some of these observations. Sánchez-Lavega et al . report that the storm developed at northern latitudes in the peak of a weak westward jet during early northern springtime. The storm head moved faster than the jet and triggered a disturbance that circled the planet. Numerical simulations show that Saturn's winds extend without decay deep down into the weather layer. Fischer et al . report that the storm reached a width of 10,000 kilometres within three weeks. Its lightning flash rates are an order of magnitude greater than those seen in previous storms, peaking at more than 10 flashes per second. Convective storms occur regularly in Saturn’s atmosphere 1 , 2 , 3 , 4 . Huge storms known as Great White Spots, which are ten times larger than the regular storms, are rarer and occur about once per Saturnian year (29.5 Earth years). Current models propose that the outbreak of a Great White Spot is due to moist convection induced by water 5 , 6 . However, the generation of the global disturbance and its effect on Saturn’s permanent winds 1 , 7 have hitherto been unconstrained 8 by data, because there was insufficient spatial resolution and temporal sampling 9 , 10 , 11 to infer the dynamics of Saturn’s weather layer (the layer in the troposphere where the cloud forms). Theoretically, it has been suggested that this phenomenon is seasonally controlled 5 , 9 , 10 . Here we report observations of a storm at northern latitudes in the peak of a weak westward jet during the beginning of northern springtime, in accord with the seasonal cycle but earlier than expected. The storm head moved faster than the jet, was active during the two-month observation period, and triggered a planetary-scale disturbance that circled Saturn but did not significantly alter the ambient zonal winds. Numerical simulations of the phenomenon show that, as on Jupiter 12 , Saturn’s winds extend without decay deep down into the weather layer, at least to the water-cloud base at pressures of 10–12 bar, which is much deeper than solar radiation penetrates.